Analisis Pengembangan Kinerja Pegawai Pada Sub Bagian Kepegawaian Umum di Dinas Kesehatan (DINKES) Provinsi Jawa Barat - Pratama, Danick Adi; Marselina, Resya Dwi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the development of employee performance in the General Personnel Sub-Division at the West Java Provincial Health Office using a qualitative approach. Through descriptive analysis methods, data were collected through interviews, observations, and documentation studies. The results of the study indicate that employee performance can be improved through training programs, competency development, and a fair reward system. Although there are still some obstacles such as lack of coordination and a fairly high level of absenteeism, employee performance improvement programs continue to run well. Efforts to improve work quality continue to be carried out gradually in order to achieve more optimal effectiveness and efficiency in public services.